The Role of The Ninth Art to Reducing the Risk of Environmental pollution - Nasser Ahmed Hamed Mohammed (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2021)
Never Human primitive at that time have a negative impact on the environment, and he did not reach coal mines, oil wells and other polluting energy sources that cause the presence of photochemical smog, and he did not invent machines that run with petroleum products, electrical or even coal, and the subsequent industries harmful to land and marine organisms, such as the manufacture of plastic bags and wooden furniture, which results in deforestation. He wasn’t able to bury radioactive materials in the ground, or to release atomic bombs and leaks of nuclear reactors, nor to spray chemicals for agricultural crops for increasing crops, which led to the distortion of embryos and the emergence of cancer of all kinds, and at that time did not reach global warming due to the increase in the amount Carbon dioxide, methane and other ozone compounds, which caused a decline in the quality of water due to the change in the temperature of the environment surrounding the Nile, It’s result of the industrial revolution and the frequent use of perfumes and pesticides.In the light of creating the necessary awareness to maintain the child's health and upbringing properly and teaching him good behavior towards the environment in which he lives, and in an attempt reduce environmental pollution through the role assigned to the ninth art products (paper and digital), the researcher accomplished Designing a set of comics against the environmentally destructive phenomenon of pollution, published in children's books and magazines, it’s for Egyptian children.